(3LGeY GdJUGfja GdQTjOjIs - (3aVd Gddg Hf CHj GdNjQ Hf Ydj CHh GdaVd GdgePGfj , QTjO GdOhdI, Ch QTjO GdOjf,J (B716 (3g` s ((3eOQSI GdMcejI(B_ (3HJHQjR s)
(3ChdgG (B:s
(3CeG HYO aEf gPG GdcJGH GdehShe HcJGH GdJhVjMGJ s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg JYGdi hMSf Jhajbg hGdUdGI hGdSdGe Ydi SjOfG eMeO GdeUWai hBdg CLeYjf GdWjHjf GdWGgQjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B74s
(3eUOQ GbJfGA GdCUd (B:s
(3Sdje CZG (B(785) s
Keywords: (3GdeYGQa GdYGeIs